THE CORRELATION BETWEEN STUDENTS’S FIXED PHRASE MASTERY AND ARGUMENTATIVE WRITING PERFORMACE - Dinar Anggraini (Jurnal Pedagogy, 2014)
The primary goal of this research was to investigate the correlation between the students’ fixed phrase mastery and argumentative writing performance. A quantitative research was used to approach the data. The population of the research was the sophomore students of PBI. The 60 samples of this research were randomly selected by random sampling technique. The data were collected by test and documentation. In addition, an analyze relating to the correlation between the students’ fixed phrase mastery and argumentative writing performance was done by using Person Product Moment. The finding of the research indicates that there is positive and significant correlation between students’ fixed phrase mastery and argumentative writing performance. It is proved by the data illustrating that rtable for N 60 at 5% level is 0.254 and for 1% level is 0.330. Consequently, it can be shown that 0.254 < 0,788 > 0.330 or 0.254 < 0,753 > 0.330.